Mitogen-activated protein kinases regulate expression of neuronal nitric oxide synthase and neurite outgrowth via non-classical retinoic acid receptor signaling in human neuroblastoma SH-SY5Y cells - Tatsuya Fujibayashi; Yuki Kurauchi; Akinori Hisatsune; Takahiro Seki; Koichi Shudo; Hiroshi Katsuki (Elsevier, 2015)
We have previously shown that retinoic acid receptor (RAR) stimulation by an agonist Am80 recruits nitric oxide-dependent signaling via increased expression of neuronal nitric oxide synthase (nNOS) in rat midbrain slice cultures. Using neuroblastoma SH-SY5Y cells, here we investigated the mechanisms of RAR-induced nNOS expression, together with relationship between nNOS expression and neurite outgrowth. Am80 promoted neurite outgrowth, which was attenuated by inhibitors of phosphoinositide 3-kinase (PI3K; LY294002), c-Jun N-terminal kinase (JNK; SP600125) and p38 mitogen-activated protein kinase (p38 MAPK; SB203580). A selective nNOS inhibitor 3-bromo-nitroindazole also suppressed Am80-induced neurite outgrowth. Am80-induced increase in nNOS protein expression was attenuated by LY294002, SP600125 and SB203580, whereas increase in nNOS mRNA expression was attenuated only by LY294002. Am80-induced activation of JNK and p38 MAPK was blocked by LY294002, suggesting that these kinases acted downstream of PI3K. We also confirmed that DAX1, a nuclear receptor reported to regulate nNOS expression, was up-regulated in response to Am80. siRNA-mediated knockdown of DAX1 abrogated Am80-induced nNOS expression and neurite outgrowth. These results reveal for the first time that nNOS expression is crucial for RAR-mediated neurite outgrowth, and that non-genomic signaling such as JNK and p38 MAPK is involved in RAR-mediated nNOS expression.